2020
DOI: 10.1002/gj.3950
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of the Palaeocene‐Eocene Upper Kelalan Formation, NW Borneo: Implications on palaeoweathering, tectonic setting, and provenance

Abstract: The stratigraphic records of Palaeocene-Eocene are studied with interest as they encompass significant high-resolution information on the environmental and climatic signals. Here, we present whole-rockgeochemistry, mineralogy, and petrography of the turbiditic sedimentary rocks of the Upper Kelalan Formation, NW Borneo, and constraints on palaeoweathering, tectonic setting, and provenance. These are finemedium-grained, poor to moderately sorted, angular to sub-rounded litharenites with lesser occurrences of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 121 publications
(155 reference statements)
1
3
0
Order By: Relevance
“…By putting all possible tectonic settings together, the findings of this study give an overview that the Eocene turbidite sediments of Bawang Member were mainly derived from felsic to mix sources and that the analysed samples belong to the active continental margin with slight passive margin involvement. A somewhat similar tectonic setting for the nearby region has also been reported quite recently, which also strengthens the presented results (Ramasamy et al, 2020).…”
Section: Regional Tectonic Implicationsupporting
confidence: 93%
See 1 more Smart Citation
“…By putting all possible tectonic settings together, the findings of this study give an overview that the Eocene turbidite sediments of Bawang Member were mainly derived from felsic to mix sources and that the analysed samples belong to the active continental margin with slight passive margin involvement. A somewhat similar tectonic setting for the nearby region has also been reported quite recently, which also strengthens the presented results (Ramasamy et al, 2020).…”
Section: Regional Tectonic Implicationsupporting
confidence: 93%
“…The comparative results of elemental ratios (Table 4) are showing that the provenance of Bawang Member is more likely to be a felsic to upper continental rather than the mafic-rich source. The previous literature (Galin et al, 2017;Hennig-Breitfeld et al, 2019;Ramasamy et al, 2020;Shen et al, 2020) reported that the main provenance of the Belaga Formation is from the Schwaner Mountains along with some material being derived from West Borneo and the Tin Belt. The felsic source for Bawang Member (Belaga Formation) is in accordance with the previously proposed source (Schwaner Mountains) of the Rajang Group.…”
Section: Provenancementioning
confidence: 99%
“…Recently, based on the geochemical composition of Neogene‐Quaternary sediments, Verma and Armstrong‐Altrin (2016) proposed discriminant‐function‐based multidimensional diagrams for the discrimination of active and passive margin settings. Such isometric log‐ratio transformations of major and major‐trace element concentrations have been successfully used (Nagarajan, Armstrong‐Altrin, Kessler, & Jong, 2017; Ramasamy et al, 2020). The active margin field includes sediments from arc and collision settings while the passive margin field includes sediments from the rift setting.…”
Section: Discussionmentioning
confidence: 99%
“…Late Cretaceous -Late Eocene mudstones of the Rajang Group, Kuching Supergroup and the Lubok Antu mélange are characterized by Chondrite-normalized LREE-enriched REE patterns and negative Eu anomalies, and the UCC-normalized trace element patterns show a Sr negative (Fig. 6a, 6b; Ferdous & Farazi, 2016;Ramasamy et al, 2021;Ahmed et al, 2021;Baioumy et al, 2021;Zhao et al, 2021;Zhu et al, 2021). In the Zr-TiO 2 provenance discrimination diagram, samples from the Kayan and Ketungau Groups of the Kuching Supergroup plot in the felsic region, and Lubok Antu Mélange samples and the Lower Rajang Group (Lupar Formation, Layar Member and Lower Kapit Member) are closer to the intermediate region, while samples from the Upper part of the Rajang Group mostly fall into the felsic region (Fig.…”
Section: Semi-quantify the Provenance Contribution Of The Rajang Grou...mentioning
confidence: 99%